The Correlation between Liver Enzymes, Red Cell Distribution Width and Mean Platelet Volume in Gestational Diabetes - Abd, Sarah Najim; Shakr, Dr. Ahmed Rifat (Journal of Science in Medicine and Life, 2025)
Background: Gestational diabetes mellitus is defined as any degree of glucose intolerance with onset or first recognition during pregnancy. It is the most common metabolic complication of pregnancy; in the Middle East, it represents 27.6% of all pregnant women. Evidence of inflammatory dysregulation (i.e., an imbalance between pro- and anti-inflammatory mediators) can be observed as early as the first trimester among pregnant women who later develop gestational diabetes mellitus. The serum levels of the liver function test parameters are generally reduced during normal pregnancy compared to the non-pregnant state, owing to the expansion of the extracellular fluid compartment, except for alkaline phosphatase, which is increased in the third trimester due to increasing placental production. Increased red cell distribution width values reflect greater variability in RBC size, which is associated with advanced fibrosis in non-alcoholic fatty liver disease. The increased production of platelets is accompanied by a reduction in their mean volume, which happened mainly in inflammatory conditions. Aim of the study: To assess the correlation between Liver enzymes, red cell distribution width, and mean platelet volume in gestational diabetes. Patients and methods: A case-control study was conducted in Al-Elwiya Maternity Teaching Hospital Department of Obstetrics and Gynecology, over a period extending from the 1st of June 2021 to the 1st of June 2022. Data obtained from the obstetrical consulting clinic were patients attained for antenatal care visits. One hundred term pregnant women with gestational diabetes were enrolled in the study as a case group. Other one-hundred-term pregnant women without gestational diabetes as a control group. Results: The mean maternal and gestational ages, gravidity, parity, and miscarriage were not different between the two groups. The mean body mass index was higher in case group than control Regarding investigations, the fasting blood glucose, glycosylated hemoglobin, liver enzymes, and red cell distribution width, were significantly higher in case group in comparison to the control, mean platelet volume was significantly lower in case group than control, while total serum bilirubin, white blood cells, and hemoglobin were not different. The mean platelet volume ≤ 8.35 fL is associated with 87% sensitivity and 81% specificity. Conclusion: Cases of gestational diabetes had higher body mass index, liver enzymes, and red cell distribution width, with low mean platelet volume level. mean platelet volume level ≤8.35 fL had 87% sensitivity and 81% specificity for marking gestational diabetes at time of delivery.